1995
DOI: 10.1073/pnas.92.16.7411
|View full text |Cite
|
Sign up to set email alerts
|

Re-expression of the alpha 2 beta 1 integrin abrogates the malignant phenotype of breast carcinoma cells.

Abstract: To assess the role of altered a2I18 integrin expression in breast cancer, we expressed the a2d31 integrin de novo in a poorly differentiated mammary carcinoma that expressed no detectable a2-integrin subunit. Expression of the a2131 integrin resulted in a dramatic phenotypic alteration from a fibroblastoid, spindle-shaped, non-contact-inhibited, motile, and invasive cell to an epithelioid, polygonal-shaped, contact-inhibited, less motile, and less invasive cell. Although expression of the a2 subunit did not al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
163
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(172 citation statements)
references
References 24 publications
6
163
1
Order By: Relevance
“…4,5,15,47 We have also shown that reexpression of the ␣ 2 ␤ 1 integrin in a poorly differentiated, invasive breast carcinoma cell line greatly diminishes, but does not completely abrogate, the malignant potential in vivo. 15 This critical observation that ␣ 2 ␤ 1 integrin expression is required for maintenance of the differentiated epithelial phenotype and glandular differentiation in vitro has been confirmed by others. The ␣ 2 ␤ 1 integrin appears to play a similar role in the morphological differentiation of colonic epithelial cells and renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…4,5,15,47 We have also shown that reexpression of the ␣ 2 ␤ 1 integrin in a poorly differentiated, invasive breast carcinoma cell line greatly diminishes, but does not completely abrogate, the malignant potential in vivo. 15 This critical observation that ␣ 2 ␤ 1 integrin expression is required for maintenance of the differentiated epithelial phenotype and glandular differentiation in vitro has been confirmed by others. The ␣ 2 ␤ 1 integrin appears to play a similar role in the morphological differentiation of colonic epithelial cells and renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 79%
“…2,3,[11][12][13][14] The important role that the ␣ 2 ␤ 1 integrin plays in normal epithelial differentiation has been substantiated by a number of in vitro "gain-offunction" and "loss-of-function" models. 4,5,15,16 For example, when a full-length ␣ 2 integrin cDNA was introduced into a poorly differentiated, tumorigenic murine breast cancer cell line that expressed no detectable ␣ 2 integrin subunit but high levels of the ␣ 1 integrin subunit, reexpression of the ␣ 2 ␤ 1 integrin resulted in dramatic phenotypic alteration from a fibroblastoid, spindleshaped, non-contact-inhibited cell to an epithelioid, polygonal-shaped, and contact-inhibited cell in culture. 15 Although the adhesion to collagen (mediated by the ␣ 1 ␤ 1 integrin) of the parental and control cells was comparable to the adhesion of the ␣ 2 transfectants, only the ␣ 2 transfectants formed organized structures, including alveolarlike and elongated multilayered duct-like structures in three-dimensional floating collagen gels.…”
mentioning
confidence: 99%
“…In transformed CHO cells, co-expression of a5 and b1 integrin rendered the cells non-tumorigenic (Giancotti and Ruoslahti, 1990). Transfection of a2 into a b1 integrin expressing mammary carcinoma cell line markedly reduced its tumorigenicity in vivo (Zutter et al, 1995). The GERM 116 cells express a5b1 integrin, yet they are as tumorigenic as the b1-de®cient parental cell line.…”
Section: Discussionmentioning
confidence: 97%
“…The present study confirms and extends our previous studies to demonstrate that MT1-MMP stimulates ERK activation in 3-D collagen, which is indispensable for proliferation of cancer cells. It is well documented that the interaction between collagen fibrils and integrin α 2 β 1 generates the growth-suppressive signals in normal epithelial or cancer cells cultured in 3-D collagen [7,[20][21][22], which can be abrogated by pericellular collagenolysis [14,15]. We represent that MT1-MMP induces c-Src activation in 3-D collagen by modulating extracellular microenvironment, which subsequently activates paxillin to scaffold signaling molecules for ERK pathway and thus leads to escape cells from growth-suppressive signals.…”
Section: Discussionmentioning
confidence: 76%